Becoming socialized in student affairs administration. - Tull, Ashley, 1972-; Hirt, Joan B.; Saunders, Sue A. (Sue Ann), 1950- (Stylus Publishing, 2011)
Effective socialization of new student affairs professionals is essential--both for the individual success of these practitioners, and for the work of a college or university that promotes student learning. It enables new professionals to manage the important personal and professional transitions they experience throughout their careers, engage in continuous professional development, and achieve high levels of productivity. It also counteracts the high attrition rate among new hires, with all the attendant costs to the institution in terms of resources spent on recruiting, hiring, training, supervising, and developing staff talent. The socialization process for new professionals includes formal and informal elements that influence both success and quality of work life. This process is far more complex than a single orientation program organized by a unit or division. Rather, it is a comprehensive process where both the new professional and organization learn about and from each other in ways that influence working relationships and individual and organizational outcomes. -- Provided by publisher.